A summary of biodiesel production over as-prepared catalyst transformed from cost-effective clays - Hiep, Dang Tan; Trang, Nguyen Thi Huyen; Chen, Bing-Hung (Vietnam Journal of Science and Technology, 2015)
This study summarized biodiesel production over as-synthesized catalysts transformed from low-cost mineral clays. The porous catalytically materials were obtained by base activation in a simple ways. It was successful to reach to high conversion efficiency (ca. 95-99%) of trans-esterification of triglycerides/vegetable oils to fatty methyl acid esters (FAMEs) - main components of biodiesel.